THE INFLUENCE OF NATIONAL CULTURE ON ORGANIZATIONAL CHANGE AND COMPETITIVENESS IN SERBIA - Ostojić, Đorđe B (International Journal of Economic Practice and Policy, 2015)
Globalization of business has created a worldwide market where companies from around the world make interactions. National cultures have a significant influence on the way companies do business, as well as on company’s market position. National culture influences the way managers interpret their environment, the types of organizational changes and employee motivation. Companies must perform more rigorous selection of workers, so as to employ a worker whose individual cultural values (that are formed under the influence of national culture) correspond to organizational culture of a company, improving the competitiveness of companies in the process.